Hidravlika za mehatronike - Lovrec, Darko; Tič, Vito (2018)
Hydraulics for Mechatronics. The Hydraulics Manual for Mechatronics, intended for students of the Mechatronics University program, provides basic information on the structure of hydraulic systems, the transmission of power, forces, motions and signals using a hydraulic fluid. In this regard, the focus is on the characteristics that must be known by those who are engaged in the automation of these systems. Those who are only meeting this technique will get the first information, and those with specific experience will be able to upgrade them. Therefore, in the presentation of individual characteristics, complex mathematical equations and derivatives are not widely used. In part, it also deals with more in-depth, especially in the themes necessary for understanding the background of the operation of the device and the structure of the individual component needed for the design of the electric control or regulation, the appropriate concept of control and control of the hydraulic system. For each chapter and for components, the basic versions and related information are first given in order to understand the basic principles and specificities. This information is supplemented with information of an "electric character" required for the construction, management, supervision and maintenance of such systems by an expert who is faced with the management and control of such systems.
Keywords: hydraulic systems; structure and characteristics; physical background of action; hydraulic fluids; components for the conversion and control of hydraulic energy; electrical and other components; meters and signals; Safety of machines and devices